Simulation based on system dynamics for evaluating the quality of transport service in a complex social system (2013)
This report presents the creation and simulation of a model based on system dynamics, applied to a complex system, in this case a system of urban public transport for medium-sized cities, evaluating the service quality variables based on comfort and speed. Simulation was performed in four scenarios, in which the value of the variable “Time interval of dispatches” was modifi ed, as it corresponds to an attribute of the operational planning of transport and is subjected to change without altering the physical infrastructure of the road network. This analysis showed the necessity of changing the interval when sending vehicles at peak hours to improve service quality.